Science teachers’ instructional practices: a need analysis for preparing integrated STEM practices through scientist-teacher-student partnership / Mohamad Hisyam Ismail ... [et al.] - Ismail, Mohamad Hisyam; Mohd Fadzil, Hidayah; Mat Salleh, Muhamad Furkan; Mohd Saat, Rohaida; Kurniawan, Cepi; Hariyono, Eko (Universiti Teknologi MARA, 2024)
The declining number of students choosing STEM subjects and careers in Malaysia has raised concern about the education system’s ability to produce sufficient human development for sound national development. The teaching approach used by the teachers to integrate STEM in the classroom practices is often claimed as one of the main determining factors contributing to this issue. Concerning this issue, this qualitative study aimed to investigate science teachers’ practices in integrating STEM in their classrooms. The interviews were conducted with six science teachers from various secondary schools in Malaysia who represented three major disciplines (Biology, Physics, and Chemistry). The purposive sampling technique was employed to select six science teachers who were involved in this study. As part of a larger study, the objectives of this study were mainly focused on exploring the instructional practices by the teachers to integrate STEM content in their classrooms, where constant comparative methods were used for data analysis. Three themes emerged from the interviews, namely, (1) instructional strategy, (2) elements of STEM, and (3) issues of the practice. The study found that all science teachers have different strategies to integrate STEM into their classrooms, such as inquiry-based and problem-based learning. To integrate STEM disciplines, the teachers are mostly focused on embedding STEM skills through hands-on activity or highlighting the real-life applications of the STEM concepts during the lesson. Less emphasis is given on connecting concepts of different disciplines during teaching and learning, and teacher-driven activities were among the issues discovered in teachers’ instructional practices. Despite their efforts, they admitted that they still lack the skills to integrate STEM and need help from experts, mainly from STEM practitioners like scientists and engineers. The study concludes that science teachers need to improve their delivery of STEM subjects more effectively. Moreover, the findings could assist stakeholders, particularly teacher training institutions, in re-assessing their education programs for current demand.